Emerging trends and focus of Toll-like receptors in kidney diseases: a 20-year bibliometric analysis - Liu, Peihan; Luo, Xinyao; Wan, Dingyuan; Li, Yupei; Su, Baihai (Frontiers in Medicine, 2025)
BackgroundAn increasing number of studies have explored the role of Toll-like receptors (TLRs) in the pathogenesis of kidney diseases and their corresponding therapeutic potential. However, there is no comprehensive bibliometric analysis in this field. This study aims to investigate the hotspots and evolution of TLRs and kidney disease research over the past two decades.MethodsPublications from the Web of Science Core Collection database were searched and extracted on December 21, 2024 using the terms “Toll-like receptor” and “kidney disease” (and their synonyms in MeSH). CiteSpace was used to explore publications from January 1, 2000, to December 21, 2024, to visualize the contributions of countries, institutions, journals, and authors, and to detect the evolution of research focus and emerging trends in this field.ResultsA total of 2,505 studies with 101,150 references were included in this study. The United States and China are the leading forces among all countries. The Egyptian Knowledge Bank is the leading institution, and Hans-Joachim Anders is considered the most influential expert in this field. PLOS One is the journal with the most publications, and Journal of Immunology is the most co-cited journal. According to the co-citation analysis, COVID-19 is the latest research hotspot. Additionally, both ischemia-reperfusion injury and diabetic nephropathy have been long-standing research hotspots and still hold significant values. Moreover, the use of TLR inhibitors as a therapeutic strategy for kidney diseases is increasingly emphasized.ConclusionOur study demonstrates a growing understanding of the crucial role of TLRs in kidney diseases over the past two decades. Future research should attach more importance to the identification of novel endogenous ligands for TLRs, which will be critical for developing TLR inhibitors as a viable therapeutic strategy.